2021
DOI: 10.46292/sci20-00007
|View full text |Cite
|
Sign up to set email alerts
|

Time Burden of Bladder Management in Individuals With Spinal Cord Injury

Abstract: Background: While clean intermittent catheterization (CIC) is the gold standard for bladder management after spinal cord injury (SCI), many individuals with SCI, for reasons not fully understood, choose alternative bladder management. We hypothesized that CIC is associated with an increased time burden in individuals with SCI. Objectives: To investigate the time required to perform neurogenic bladder management in individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Time burden for self-catheterization has been previously studied, and, although women and men had similar average times for self-catheterization, women in this study had high rates (38%) of catheterizable channel creation. 25 Our study results highlight that creation of catheterizable channels in women is an important treatment option in those that want to continue CIC.…”
Section: Discussionmentioning
confidence: 68%
“…Time burden for self-catheterization has been previously studied, and, although women and men had similar average times for self-catheterization, women in this study had high rates (38%) of catheterizable channel creation. 25 Our study results highlight that creation of catheterizable channels in women is an important treatment option in those that want to continue CIC.…”
Section: Discussionmentioning
confidence: 68%
“…21 ISC and bowel management are timeconsuming and require a longer duration of management, resulting in a relatively high therapeutic burden, and are associated with a lower QOL for people with an SCI. 22,23 The potential burden of each treatment should be taken into account when considering the continuity T A B L E 3 Association between catheter maintenance and symptomatic urinary tract infection. of multiple treatments because adding an additional workload may lead to diminished self-care, lower adherence to treatments, and worse treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 1334 people with SCI in the United Kingdom showed that bowel or urinary management had a greater effect on daily life than wheelchair use or pain 21 . ISC and bowel management are time‐consuming and require a longer duration of management, resulting in a relatively high therapeutic burden, and are associated with a lower QOL for people with an SCI 22,23 . The potential burden of each treatment should be taken into account when considering the continuity of multiple treatments because adding an additional workload may lead to diminished self‐care, lower adherence to treatments, and worse treatment outcomes 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously proposed explanations for the higher rates of suprapubic catheter insertion in women include less straightforward access to the urethra, transferring difficulties [ 14 , 15 ], which along with other factors, could lead to a suprapubic catheter allowing women to have more independence [ 8 ]. In a community setting, the time required for catheterization through the urethra tended to be substantially longer for a small sample of women who were overweight or who required caregiver support [ 26 ], indicating that the suprapubic catheter might be the more convenient option for some [ 8 ]. A final factor identified in the community setting, "lack of sitting balance" was more commonly cited by females than males as an explanation of inability to perform intermittent catheterization independently [ 27 ], and this might also provide a suggestion as to why thoracic AIS grade A,B,C SCI is tentatively a female-specific predictor of suprapubic catheter use in the present study.…”
Section: Discussionmentioning
confidence: 99%